The Development of Module Containing Local Culture with Realistic Approach for Mathematical Literation of Elementary School Students (Journal of Primary Education, 2019)
This study has purpose to develop the independent learning modules that support the improvement of mathematics literacy skills of the fifth grade students of elementary school. The module developed was adjusted to the 2013 curriculum and focused on ordinary, mixed, and decimal multiplication materials, containing with local culture using the realistic approach integrated in mathematical adventure stories. This was a research and development with the Thiagaranjan 4D model that was modified into the development stage in a limited test through the steps of define, design, and develop applied to the fifth grade students of SDN Kendal Serut 02, Pangkah, Tegal. The results at the development stage showed a form of additional supplement that is suitable with the characteristics of the needs of the elementary school students, which is loaded with local culture with relevant realistic approach. At the development stage, the module is produced in developing the mathematical literacy which is considered valid by material and media experts. In addition, trials on users showed positive responses from teachers and students in grade V which showed that the Mathematical Literacy Ability of students after learning with the module was better than previous condition (P = 0.000) with an increase in N-gain of 0.4 in the medium category.